Pemanfaatan Biogas/Landfillgas Sebagai Bahan Bakar Mesin Bensin 1 Silinder 4 Langkah - Achmad Fauzan Hery; Zamzami Septiropa; Selly Riansyah; Faizal Romadhi (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
Motor gasoline also proven to be turned on by using biogas. This is done through the addition of a simple regulator to biogas, and air mixer - biogas. In practice, though not obtain maximum performance, modifiers remain to be done without changing the ignition time. Previously, the experiment was done first using LPG, LPG-and then use a mixture of biogas and biogas pure. Machine can be turned on using biogas with methane content of 56-60%. Engine fuel or motor fuel of biogas that is used in the experiment can generate electricity to turn the lights up to 300 watts. A quarter of its normal capacity when using premium fuel / gasoline. Optimal load occurs at 150 watts means the power load 150 watts, the conversion of biogas energy to be the highest power of 230 watt/m3 biogas. At 150 watts of loading the fuel consumption is 0.000097333 liters / watt.